2005
DOI: 10.1074/jbc.m503139200
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Regulates the Hypotriglyceridemic Gene APOA5

Abstract: The apolipoprotein AV gene (APOA5) is a key determinant of plasma triglyceride levels, a major risk factor for coronary artery disease and a biomarker for the metabolic syndrome. Since thyroid hormones influence very low density lipoprotein triglyceride metabolism and clinical studies have demonstrated an inverse correlation between thyroid status and plasma triglyceride levels, we examined whether APOA5 is regulated by thyroid hormone. Here we report that 3,5,3-triiodo-Lthyronine (T 3 ) and a synthetic thyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 73 publications
(81 reference statements)
2
39
0
Order By: Relevance
“…This work showed for the first time the phosphorylation-dependent binding of USF1/2 to a functional E-box element within the APOA5 promoter. Interestingly, in agreement with our study, Prieur et al 19 have reported that the thyroid hormone regulates the hypotriglyceridemic gene APOA5 through a synergistic activation with USF. Their report combinated with ours raises the possibility of a cross talk between insulin and thyroid signals on the same element in APOA5.…”
Section: Introductionsupporting
confidence: 82%
“…This work showed for the first time the phosphorylation-dependent binding of USF1/2 to a functional E-box element within the APOA5 promoter. Interestingly, in agreement with our study, Prieur et al 19 have reported that the thyroid hormone regulates the hypotriglyceridemic gene APOA5 through a synergistic activation with USF. Their report combinated with ours raises the possibility of a cross talk between insulin and thyroid signals on the same element in APOA5.…”
Section: Introductionsupporting
confidence: 82%
“…Thyroid hormones can influence lipid metabolism by: 1) inducing HMG CoA reductase; 2) controlling SREBP-2 which regulates LDL receptor expression; 3) increasing CETP activity; and 4) upregulating the synthesis of apoAV [313][314][315][316]. ANGPTL3 gene is negatively regulated by triodothyronine leading to the speculation that triodothyronine can lower plasma triglycerides by suppressing the ANGPTL3 gene thus activating LPL which plays a central role in lipid metabolism [317].…”
Section: Hormones and Lipid Metabolismmentioning
confidence: 99%
“…The most important mechanisms of thyroid hormone action on lipid metabolism are shown in (Prieur et al, 2005) Inhibition of TGs production Increased TG levels, acceleration of atherosclerosis and CAD T3 and its acetic derivative protect LDL from oxidation (Faureet al, 2004) Protection from oxidation of LDL Burden of oxidative stress, acceleration of atherosclerosis and CAD Increased cholesteryl ester transfer protein activity Increased exchange of cholesteryl esters from HDL2 to VLDL and TGs to the opposite direction (Rizos et al, 2011) Not definitely established, due to this mechanism plasma HDL levels may be elevated…”
Section: Hypothyroidism and Hyperlipidemiamentioning
confidence: 99%